Sikap Ibu Hamil Terkait Antenatal Care Dengan Penggunaan Media Maternal Cycle Simulation - Naimah Naimah; Ridzky Berliana Kusuma (Malang Journal of Midwifery (MAJORY), 2020)
Mother's concern before pregnancy to check her nutritional status is still very lacking, this will result in the undetectability of nutritional problems experienced by mothers, such as anemia and chronic energy deficiency. The study aimed to determine the attitudes of pregnant women about antenatal care using the Maternal Cycle Simulation media. The design of this study was pre-experimental with One Group Pre-Test-Post Test design. The sample used was pregnant women aged 22-28 weeks who met the inclusion and exclusion criteria of 27 people with simple random sampling technique. Health education was carried out in three meetings, including pretest and provision of media Maternal Cycle Simulation, explanation of media use, demonstration of media use, re-demonstration by pregnant women using media, re-examination and monitoring using media, and posttest. The results showed 74% of mothers had a negative attitude in antenatal care at the time of the pretest and there was a decrease in the negative attitude rate to 15% after receiving the Maternal Cycle Simulation media with a p value <0.001, which means there was an influence of the use of the Maternal Cycle Simulation media towards the attitude of pregnant women about antenatal care care. Keywords: Maternal Cycle Simulation, Antenatal Care, Attitude of Pregnant Women